Effectiveness of an intervention designed based on the Health Action Process Approach on obesity surgery outcomes in patients who have undergone bariatric surgery after one year: A randomized controlled trial - Maryam Maghsoodlo; Elham Shakibazadeh; Mehdi Yaseri; Zeinab Mokhtari; Maryam Barzin; Yahya Salimi (PLoS ONE, 2025)
Background Bariatric surgery is effective in treating severe obesity. However, surgery alone, without additional behavior change management, may not lead to optimal long-term weight loss and maintenance. This study aimed to evaluate an intervention designed based on the Health Action Process Approach to improve outcomes of obesity surgery in patients who underwent bariatric surgery in Tehran, Iran. Methods In this randomized controlled trial, a total of 100 patients who had undergone bariatric surgery after the past year were randomly assigned to two intervention (n = 50) and control (n = 50) groups. The intervention group received educational intervention for two months. Health action process approach (HAPA) constructs, the Bariatric Surgery Self-Management Behaviors Questionnaire (BSSQ), dietary recall, blood chemistry parameters, BMI, percentage of body weight loss, and the International Physical Activity Questionnaire (IPAC) were measured at baseline and four months after the intervention. To compare the changes between the two groups before and four months after the educational intervention, the interaction of group and time was analyzed using the generalized estimating equation (GEE). A p-value of less than 0.05 was considered statistically significant. Results The educational intervention resulted in improvements in various aspects of self-efficacy, including task and coping self-efficacy constructs (P = 0.02), action planning (P < 0.01) and behavioral intention (P < 0.01) related to diet self-management. There were also statistically significant improvements in action planning (P = 0.02), risk perception (P = 0.01) and Recovery self- efficacy (P = 0.01) related to the self-management of physical activity. There were significant improvements in the iron blood test results (P =  0.01) among the patients. Conclusion Our intervention, designed based on the Health Action Process Approach, led to improvements in dietary and physical activity outcomes among patients who underwent bariatric surgery. Trial Registration: Iran Randomized Clinical Trials IRCT20230722058887N1.